Marine communities of the newly created Kawesqar National Reserve, Chile: From glaciers to the Pacific Ocean - Friedlander, Alan M.; Ballesteros, Enric; Goodell, Whitney; Hune, Mathias; Munoz, Alex; Salinas-de-Leon, Pelayo; Velasco-Charpentier, Catalina; Sala, Enric (My University, 2021)
The newly created Kawesqar National Park (KNP) and National Reserve (KNR) in southern Chile consists of diverse terrestrial and marine habitats, which includes the southern terminus of the Andes, the Southern Patagonia Ice Fields, sub-Antarctic rainforests, glaciers, fjords, lakes, wetlands, valleys, channels, and islands. The marine environment is influenced by wide ranging hydrological factors such as glacier melt, large terrigenous inputs, high precipitation, strong currents, and open ocean water masses. Owing to the remoteness, rugged terrain, and harsh environmental conditions, little is known about this vast region, particularly the marine realm. To this end, we conducted an integrated ecological assessment using SCUBA and remote cameras down to 600 m to examine this unique and largely unexplored ecosystem. Kelp forests (primarily Macrocystis pyrifera) dominate the nearshore ecosystem and provide habitat for myriad benthic organisms. In the fjords, salinity was low and both turbidity and nutrients from terrigenous sources were high, with benthic communities dominated by active suspension feeders (e.g., Bivalvia, Ascidiacea, and Bryozoa). Areas closer to the Pacific Ocean showed more oceanic conditions with higher salinity and lower turbidity, with benthic communities experiencing more open benthic physical space in which predators (e.g., Malacostraca and Asteroidea) and herbivorous browsers (e.g., Echinoidea and Gastropoda) were more conspicuous components of the community compared to the inner fjords. Hagfish (Myxine sp.) was the most abundant and frequently occurring fish taxa observed on deep-sea cameras (80% of deployments), along with several taxa of sharks (e.g., Squaliformes, Etmopteridae, Somniosidae, Scyliorhinidae), which collectively were also observed on 80% of deep-sea camera deployments. The kelp forests, deep fjords, and other nearshore habitats of the KNR represent a unique ecosystem with minimal human impacts at present. The KNR is part of the ancestral territory of the indigenous Kawesqar people and their traditional knowledge, including the importance of the land-sea connection in structuring the marine communities of this region, is strongly supported by our scientific findings.
Keywords: Fjord; Marine protected area